The Middle East and North Africa and Dependence on the Capital-Intensive Hydrocarbon Sector - Ianchovichina, Elena (World Bank, Washington, DC, 2012)
MENA felt the impact of the financial and economic crisis to a much lesser extent than developed economies and emerging markets outside Asia, however, the economic recovery in MENA has also lacked vigor. Before the recent uprisings, MENA was expected to return to pre-crisis growth rates of 4.8 percent by 2011-12, but growth rates in this range are not high enough to address the key challenges facing the region, including high unemployment rates - especially for young people and low labor-force participation rates, notably for women. The region also has one of the world's lowest formal employment rates as well as the highest population and labor force growth rates among middle-income economies. To address these challenges MENA's economy should be growing at rates close to those observed in East Asia and other high performing emerging economies. It has not done so.